2021
DOI: 10.1021/acs.energyfuels.0c04287
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial and Confinement-Mediated Organization of Gas Hydrates, Water, Organic Fluids, and Nanoparticles for the Utilization of Subsurface Energy and Geological Resources

Abstract: Harnessing the subsurface geologic environments in an efficient and environmentally sustainable manner is challenged by uncertainties associated with predicting the fate of fluids and sustaining porosity and permeability in subsurface geologic environments. Some of these uncertainties arise from confined and interfacially induced structures of fluids in subsurface geologic environments. The formation of gas hydrates, phase transitions of confined fluids, assembly and deposition of heavy hydrocarbons, and the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 386 publications
0
9
0
Order By: Relevance
“…Synthetic clathrates tend to attach to equipment walls, accumulate, and finally block the reactors and circulation systems. Natural clathrates contact and interact with a variety of natural solid matters through clathrate-solid interfaces. The interaction at the interfaces influences the mechanical and physiochemical stability of the clathrate deposits. Thus, a better understanding of adhesion forces is required for exploiting natural clathrates.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic clathrates tend to attach to equipment walls, accumulate, and finally block the reactors and circulation systems. Natural clathrates contact and interact with a variety of natural solid matters through clathrate-solid interfaces. The interaction at the interfaces influences the mechanical and physiochemical stability of the clathrate deposits. Thus, a better understanding of adhesion forces is required for exploiting natural clathrates.…”
Section: Introductionmentioning
confidence: 99%
“…A queous solutions under nanoscale confinement have attracted considerable interest over the past few years, owing to their unusual structural, dynamical, and physicochemical properties (different from those of their bulk counterparts), as well as to their broad significance for nanoscale chemical, biological, and physical systems such as ion channels/ batteries and water desalination [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] . For instance, numerous experiments and molecular dynamics (MD) simulations revealed that nanoconfined water may freeze into various one-dimensional (1D) and two-dimensional (2D) polymorphous and polyamorphous structures at low temperatures 4,8,10,[16][17][18][19][20][21][22][23][24][25][26][27][28][29] .…”
mentioning
confidence: 99%
“…On the other hand, the porous material in the second approach can act as a medium for hydrate synthesis within the confinement approach. It has been found that high-pressure phases and reactions were found to occur in confined spaces in pressures that are magnitudes lower than required for bulk ones [134,135].For example, Siangsai et al…”
Section: Methane Storagementioning
confidence: 99%